RGB-image method enables indirect selection for leaf spot resistance and yield estimation in a groundnut breeding program in Western Africa - Sie, Emmanuel Kofi; Oteng-Frimpong, Richard; Kassim, Yussif Baba; Puozaa, Doris Kanvenaa; Adjebeng-Danquah, Joseph; Masawudu, Abdul Rasheed; Ofori, Kwadwo; Danquah, Agyemang; Cazenave, Alexandre Brice; Hoisington, David; Rhoads, James; Balota, Maria (Frontiers in Plant Science, 2022)
Early leaf spot (ELS) caused by the fungus Passalora arachidicola, previously known to be Cercospora arachidicola and late leaf spot (LLS) also caused by the fungus Nathopassalora personata, previously known to be Cercosporidium personatum are the two major groundnut (Arachis hypogaea L.) destructive diseases in Ghana. Accurate phenotyping and genotyping to develop groundnut genotypes resistant to leaf spot diseases (LSD) and to increase groundnut production is critically important in Western Africa. Two experiments were conducted at the Council for Scientific and Industrial Research-Savanna Agricultural Research Institute located in Nyankpala, Ghana to explore the effectiveness of using photogrammetry as a high-throughput phenotyping tool to assess groundnut LSD and to estimate yield components. Replicated plots arranged in a rectangular alpha lattice design were conducted during the 2020 growing season using a set of 60 genotypes as the training population and 192 genotypes for validation. Indirect selection models were developed using red-green-blue (RGB) color space indices. Data was collected on conventional LSD ratings, RGB imaging, pod weight per plant and number of pods per plant. Data was analyzed using a mixed linear model with R statistical software version 4.0.2. The results showed differences among the genotypes for the traits evaluated. The photogrammetry traits exhibited comparable or better broad sense heritability to the conventionally measured traits. Significant correlation existed between the photogrammetry traits and the conventionally measured traits. Six (6) models predicting ELS and LLS were proposed. Genotypes 73-33, Gha-GAF 1723, Zam-ICGV-SM 07599, and Oug-ICGV 90099 were among the most resistant genotypes to ELS and LLS, and they represent suitable sources of resistance to LSD for the groundnut breeding programs in Western Africa.